2018
DOI: 10.3389/fpsyg.2017.02338
|View full text |Cite
|
Sign up to set email alerts
|

Financial Planning for Retirement: A Psychosocial Perspective

Abstract: Retirement is a time of life that has grown ever longer in the developed world, and the number of pensioners has increased accordingly, questioning the strength of Social Security systems and the social safety net in general. Financial Planning for Retirement (FRP) consists of the series of activities involved in the accumulation of wealth to cover needs in the post-retirement stage of life. The negative short-, mid-, and long-term consequences of inadequate Financial Planning for Retirement do not only affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 62 publications
(60 reference statements)
1
46
0
1
Order By: Relevance
“…Previous studies have demonstrated that planning correlates positively with healthy financial behavior (Strömbäck et al, 2017; Topa et al, 2018). In the current study this correlation was significant but weak ( r = -0.14).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that planning correlates positively with healthy financial behavior (Strömbäck et al, 2017; Topa et al, 2018). In the current study this correlation was significant but weak ( r = -0.14).…”
Section: Resultsmentioning
confidence: 99%
“…The current study had important practical implications. There are noted gender differences in financial behavior, such as financial risk-taking, retirement saving intention and behavior (Xiao et al, 2011; Ismail et al, 2017; Magendans et al, 2017; Panno et al, 2017; Topa et al, 2018). However, there was no gender differences in the disposition effect in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we introduce the variable of financial self-efficacy (FSE), which refers to “one’s belief about their capability of organizing and executing courses of action to achieve one’s ultimate financial goals” (Forbes and Kara, 2010). Recent research has found that FSE plays an important role in a series of financial decisions, such as financial inclusion (Mindra and Moya, 2017), financial planning for retirement (Topa et al, 2018), saving behavior (Xiao et al, 2011; Ismail et al, 2017; Magendans et al, 2017), and financial satisfaction (Asebedo and Payne, 2018). However, a few studies have investigated the association between FSE and the disposition effect.…”
Section: Introductionmentioning
confidence: 99%
“…The aspects of pensioners' economic mind are still poorly studied. There are attempts to develop a financial planning model for pensioners taking into account their capabilities, abilities, and wishes [19].…”
Section: Theoretical Frameworkmentioning
confidence: 99%